2004
DOI: 10.1136/bmj.38285.482350.82
|View full text |Cite
|
Sign up to set email alerts
|

Comparing estimates of cost effectiveness submitted to the National Institute for Clinical Excellence (NICE) by different organisations: retrospective study

Abstract: Objective To assess the association between different types of organisation and the results from economic evaluations. Design Retrospective pairwise comparison of evidence submitted to the technology appraisal programme of the National Institute for Clinical Excellence (NICE) by manufacturers of the relevant healthcare technologies and by contracted university based assessment groups. Data sources Data from the first 62 appraisals. Main outcome measure Incremental cost effectiveness ratios. Results Data from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 11 publications
2
42
0
Order By: Relevance
“…Such differences should theoretically not be so apparent within NICE's TAP, as the manufacturer and AG estimates of the ICER are calculated at the same time, often using the same studies to populate the economic analysis; however, Miners et al observed that the technology manufacturers submitting to NICE made claims of better cost-effectiveness compared with university-based AGs (8).…”
Section: Discussionmentioning
confidence: 99%
“…Such differences should theoretically not be so apparent within NICE's TAP, as the manufacturer and AG estimates of the ICER are calculated at the same time, often using the same studies to populate the economic analysis; however, Miners et al observed that the technology manufacturers submitting to NICE made claims of better cost-effectiveness compared with university-based AGs (8).…”
Section: Discussionmentioning
confidence: 99%
“…Cost-effectiveness analysis is a tool that can help to shift away from or avoid therapies that produce too little benefit at too high cost. Presently, there is no consensus regarding the appropriate threshold value, but a range of $50 000-100 000 per gained life year is commonly used in the United States (Hillner et al, 2005) and in UK, a threshold of d30 000 (approximately $55,000) has been suggested (Miners et al, 2005). N9741 demonstrated that FOLFOX was superior to the previous standard of care in the United States, IFL .…”
Section: Costmentioning
confidence: 99%
“…2 Examples exist in which cost-effectiveness analysis studies on the same topic have reached different conclusions depending on who funded them. 3 Yet the mechanism for such discrepancies in seemingly rigorous quantitative analyses is unclear.…”
mentioning
confidence: 99%